2022
DOI: 10.1186/s12905-022-01709-x
|View full text |Cite
|
Sign up to set email alerts
|

Unmet need for family planning among married women in Zambia: lessons from the 2018 Demographic and Health Survey

Abstract: Background Unmet need for family planning among married women is still a public health concern in sub-Saharan Africa. In Zambia, one in every five married women had an unmet need for family planning in 2018. Unmet need for family planning has the potential to increase the number of unintended pregnancies and unsafe abortions. These factors can increase the proportion of women of child bearing age, who are at high risk of birth complications. This study was therefore conducted to understand the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
6
8
0
Order By: Relevance
“…Similar to our findings, studies in Tigray [ 36 ] and Dire Dawa [ 38 ] in Ethiopia, Nigeria [ 34 ] and India [ 41 ] found that women living with HIV residing in rural areas were more likely to have unmet need for family planning than their counterparts from the urban areas. The probable explanation for this phenomenon is that women in rural areas have lower exposure to information and limited access to sexual and reproductive health services than their urban counterparts, as reported in surveys in Zambia and elsewhere [ 30 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar to our findings, studies in Tigray [ 36 ] and Dire Dawa [ 38 ] in Ethiopia, Nigeria [ 34 ] and India [ 41 ] found that women living with HIV residing in rural areas were more likely to have unmet need for family planning than their counterparts from the urban areas. The probable explanation for this phenomenon is that women in rural areas have lower exposure to information and limited access to sexual and reproductive health services than their urban counterparts, as reported in surveys in Zambia and elsewhere [ 30 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Our analysis revealed that geographical residence (rural versus urban), age of a woman, socioeconomic status, number of children ever born to a woman (parity), employment status and partner’s age constituted factors significantly associated with unmet need for family planning. These findings are largely consistent with other studies [ 34 38 ] including a Zambian study which analysed unmet need for family planning using the 2018 DHS data [ 34 ]. From a review of literature, predictors of contraceptive uptake and unmet need for family planning are similar for HIV positive and HIV negative women.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The result was partially consistent with a study in Zambia, where women with 0 or 1 child were less likely to have an unmet need compared to women with ≥ 4 children, while there were no differences between women with 0 or 1 child and women with 2 or 3 children. (25) This might be because of the difference in variable categorization between our study and that of Zambia. The study in Zambia divided the categories into four subgroups (0-1 child, 2-3 children, 4-5 children and ≥ 6 children), (25) whereas in our study, four subgroups were divided differently (0 child, 1 child, 2 children, and ≥ 3 children).…”
Section: Resultsmentioning
confidence: 81%
“…(25) This might be because of the difference in variable categorization between our study and that of Zambia. The study in Zambia divided the categories into four subgroups (0-1 child, 2-3 children, 4-5 children and ≥ 6 children), (25) whereas in our study, four subgroups were divided differently (0 child, 1 child, 2 children, and ≥ 3 children). In this study, the higher the number of children, the higher the likelihood that women had an unmet need for contraception.…”
Section: Resultsmentioning
confidence: 81%